Kekuatan Pembuktian Akta Pengakuan Utang oleh Direksi dalam Proses Penundaan Kewajiban Pembayaran Utang - Larasati, Andien; Raden Besse Kartoningrat (Fakultas Hukum Universitas Airlangga, 2024)
In this research, the author discusses the legal force of proof of a debt acknowledgement deed made by the Directors of a Limited Liability Company which violates the Articles of Association by analyzing a decision of Postponement of Debt Payment Obligations. The Directors, as a Debtors in this case, together with the notary, manipulated the debt acknowledgement deed as form a documentary evidence, the proof of which contained formal and material defects whose veracity could not be justified, so that it would be detrimental to both themselves and the opposing party. The author's aim in writing this research is so that later readers can understand the legal strength of evidence of authentic deeds manipulated in this process. The existence and urgency a debt acknowledgement deed for the Debtor as evidence in court will also be explained by the author. Based on the title of this research, the author will use the statutory regulatory approach and case approach in solving this legal problem.